2016
DOI: 10.1177/0308518x16669353
|View full text |Cite
|
Sign up to set email alerts
|

Study tours and inter-city policy learning: Mobilizing Bogotá’s transportation policies in Guadalajara

Abstract: While modern urban planning has traditionally been shaped by policies and instruments from European and North American cities, in recent decades there has been an increase in South-South policy learning and a number of cities of the global South have emerged as alternative urban planning models. Yet, less is known about the practices through which urban policy actors in cities of the South learn from other Southern cities’ policies. This paper examines the case of Guadalajara, Mexico, where different local pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…Crowfoot's statement on how his understanding of the program changed after he 'actually saw it' in the video is similar to that of participants in Bogotá study tours, who often refer to these tours as 'eye-opening' experiences (Montero, 2017a). This suggests that part of the agency of digital videos to promote policy change relies not only on transmitting the Bogotá story but also on its capacity to make odd ideas seem common sense.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Crowfoot's statement on how his understanding of the program changed after he 'actually saw it' in the video is similar to that of participants in Bogotá study tours, who often refer to these tours as 'eye-opening' experiences (Montero, 2017a). This suggests that part of the agency of digital videos to promote policy change relies not only on transmitting the Bogotá story but also on its capacity to make odd ideas seem common sense.…”
mentioning
confidence: 81%
“…However, digital materials do not simply float around on the internet. Similar to the organization of other infrastructures of policy learning and circulation, such as conferences or study tours (González, ; Cook and Ward, ; Montero, ), it is important to situate the production and circulation of digital materials within a political economy that is both local and transnational.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mobile best practices as well as informational infrastructure events can lead to material changes -big and small, positive and negative, for many people inside and outside of policymaking circles. To give an example, Wood (2014) and Montero (2017) have shown that study tours can enhance the learning of those attending, strengthen social bonds between participants, and inform policy recommendations. One often-overlooked material impact should not be forgotten and it will be closely examined in this paper: that of informational infrastructure events on the institutions that host the events.…”
Section: Transformative Best Practice Models and Eventsmentioning
confidence: 99%
“…In definitional terms, policy tourism can be defined as "policy actors travell [ing] elsewhere to see, first-hand, the implementation and consequences of particular policies and to learn directly from those involved in their development and implementation" (Temenos & McCann, 2013, p. 34). While policy actors have more opportunity than ever before to learn at a distance, a growing array of studies document the persistent appeal of being physically proximate to the ideas and programmes that policy actors wish to understand and, potentially, emulate (Clifford & Morphet, 2014;Cook et al, 2015;Evans, 2009;Montero, 2017). While policy actors have more opportunity than ever before to learn at a distance, a growing array of studies document the persistent appeal of being physically proximate to the ideas and programmes that policy actors wish to understand and, potentially, emulate (Clifford & Morphet, 2014;Cook et al, 2015;Evans, 2009;Montero, 2017).…”
Section: The Popularity Of Policy Tourismmentioning
confidence: 99%